SEC62 encodes a putative membrane protein required for protein translocation into the yeast endoplasmic reticulum (The Rockefeller University Press, 1989)
Yeast sec62 mutant cells are defective in the translocation of several secretory precursor proteins into the lumen of the endoplasmic reticulum (Rothblatt et al., 1989). The deficiency, which is most restrictive for alpha-factor precursor (pp alpha F) and preprocarboxypeptidase Y, has been reproduced in vitro. Membranes isolated from mutant cells display low and labile translocation activity with pp alpha F translated in a wild-type cytosol fraction. The defect is unique to the membrane fraction because cytosol from mutant cells supports translocation into membranes from wild-type yeast. Invertase assembly is only partly affected by the sec62 mutation in vivo and is nearly normal with mutant membranes in vitro. A potential membrane location for the SEC62 gene product is supported by evaluation of the molecular clone. DNA sequence analysis reveals a 32- kD protein with no obvious NH2-terminal signal sequence but with two domains of sufficient length and hydrophobicity to span a lipid bilayer. Sec62p is predicted to display significant NH2- and COOH- terminal hydrophilic domains on the cytoplasmic surface of the ER membrane. The last 30 amino acids of the COOH terminus may form an alpha-helix with 14 lysine and arginine residues arranged uniformly about the helix. This domain may allow Sec62p to interact with other proteins of the putative translocation complex.